Partial Androgen Deficiency, Depression, and Testosterone Supplementation in Aging Men - Mario Amore; Marco Innamorati; Sara Costi; Leo Sher; Paolo Girardi; Maurizio Pompili (International Journal of Endocrinology)
The aim of this review was to summarize current knowledge on the correlation between depressive symptoms with a syndrome called partial androgen deficiency of the aging male (PADAM) and on the potential benefits of testosterone (T) treatment on mood. Despite, the causative nature of the relationship between low T levels and depression is uncertain, many hypogonadal men suffer from depression and vice versa several depressed patients are affected by hypogonadism. Supplementation with testosterone failed to show sound evidence of effectiveness in the treatment of depression. Nevertheless, testosterone supplementation has proved to be effective on some domains significant for the quality of life of aged patients with PADAM (sexual function and cognitive functions, muscular strengths).